In Defense of the Land Ethic - Callicott, J. Baird; Callicott, J. Baird (State University of New York Press, 1989)
Human ecology-Moral and ethical aspects; Environmental protection; Leopold, Aldo, 1887-1948
English
Keywords: 9; Climate Crisis